GA Houses 187. - Futagawa, Yoshio; Hitomi, Saito (Tokyo : A.D.A. EDITA Tokyo Co., Ltd., 2023)
The special issue ‘Project 2023’ features more than 50 ongoing residential works from around the globe. Filled with drawings, models, concepts, and detailed profiles of some of the most innovative and challenging residential architecture currently being imagined by a diverse group of architects and design studios, it includes projects by Aires Mateus, Tadao Ando, Ensamble Studio, Steven Holl, Sean Godsell, Kengo Kuma, Kazuyo Sejima, and many more.
boek